Influx mechanisms in the embryonic and adult rat choroid plexus: a transcriptome study - Saunders, Norman R.; Dziegielewska, Katarzyna M.; Møllgård, Kjeld; Habgood, Mark D.; Wakefield, Matthew J.; Lindsay, Helen; Stratzielle, Nathalie; Ghersi-Egea, Jean-Francois; Liddelow, Shane A. (Frontiers in Neuroscience, 2015)
The transcriptome of embryonic and adult rat lateral ventricular choroid plexus, using a combination of RNA-Sequencing and microarray data, was analyzed by functional groups of influx transporters, particularly solute carrier (SLC) transporters. RNA-Seq was performed at embryonic day (E) 15 and adult with additional data obtained at intermediate ages from microarray analysis. The largest represented functional group in the embryo was amino acid transporters (twelve) with expression levels 2–98 times greater than in the adult. In contrast, in the adult only six amino acid transporters were up-regulated compared to the embryo and at more modest enrichment levels (<5-fold enrichment above E15). In E15 plexus five glucose transporters, in particular Glut-1, and only one monocarboxylate transporter were enriched compared to the adult, whereas only two glucose transporters but six monocarboxylate transporters in the adult plexus were expressed at higher levels than in embryos. These results are compared with earlier published physiological studies of amino acid and monocarboxylate transport in developing rodents. This comparison shows correlation of high expression of some transporters in the developing brain with higher amino acid transport activity reported previously. Data for divalent metal transporters are also considered. Immunohistochemistry of several transporters (e.g., Slc16a10, a thyroid hormone transporter) gene products was carried out to confirm translational activity and to define cellular distribution of the proteins. Overall the results show that there is substantial expression of numerous influx transporters in the embryonic choroid plexus, many at higher levels than in the adult. This, together with immunohistochemical evidence and data from published physiological transport studies suggests that the choroid plexus in embryonic brain plays a major role in supplying the developing brain with essential nutrients.